TANGGUNG JAWAB PENGANGKUT ATAS MUSNAHNYA BARANG AKIBAT TENGGELAMNYA KAPAL KLM PULAU BONTONG BERDASARKAN UNDANG-UNDANG NOMOR 17 TAHUN 2008 TENTANG PELAYARAN (STUDI KASUS: PUTUSAN NOMOR 804/Pdt.G/2017/PN JKT.SEL) - Noviana Annisa; Siti Nurbaiti (Jurnal Hukum Adigama, 2020)
In marine transportation activities there are several things that must be considered by carries before sailing. One of them is the issue of the Port Clearance issued by Syahbandar as one of the proofs that the ship is seaworthy. However, the carrier does not pay attention to the feasibility of the ship to sail which will cause a ship accident. The main problem is the issue of responsibility that transports the KLM Pulau Bonrong ship to the goods transported. Researchers discuss problems by using normative legal research methods and using laws, as well as asking questions and asking for conceptual. Research data shows that KLM Pulau Bontong transporters must be responsible to the sender for the good they carry are not safe until the destination of the KLM Pulau Bontong ship accident in Pulau Seraya. The carrier is responsible for the accident by providing compensation for the assistance of goods worth the loss suffered.